Effects of ranolazine on right ventricular function, fluid dynamics, and metabolism in patients with precapillary pulmonary hypertension: insights from a longitudinal, randomized, double-blinded, placebo controlled, multicenter study - Han, Q. Joyce; Forfia, Paul; Vaidya, Anjali; Ramani, Gautam; deKemp, Robert A.; Mach, Robert H.; Mankoff, David A.; Bravo, Paco E.; DiCarli, Marcelo; Chan, Stephen Y.; Waxman, Aaron B.; Han, Yuchi (Frontiers in Cardiovascular Medicine, 2023)
Right ventricular (RV) function is a major determinant of outcome in patients with precapillary pulmonary hypertension (PH). We studied the effect of ranolazine on RV function over 6 months using multi-modality imaging and biochemical markers in patients with precapillary PH (groups I, III, and IV) and RV dysfunction (CMR imaging ejection fraction [EF] <45%) in a longitudinal, randomized, double-blinded, placebo-controlled, multicenter study of ranolazine treatment. Enrolled patients were assessed using cardiac magnetic resonance (CMR) imaging, 11C-acetate and 18-F-FDG positron emission tomography (PET), and plasma metabolomic profiling, at baseline and at the end of treatment. Twenty-two patients were enrolled, and 15 patients completed all follow-up studies with 9 in the ranolazine arm and 6 in the placebo arm. RVEF and RV/left ventricle (LV) mean glucose uptake were significantly improved after 6 months of treatment in the ranolazine arm. Metabolomic changes in aromatic amino acid metabolism, redox homeostasis, and bile acid metabolism were observed after ranolazine treatment, and several changes significantly correlated with changes in PET and CMR-derived fluid dynamic measurements. Ranolazine may improve RV function by altering RV metabolism in patients with precapillary PH. Larger studies are needed to confirm the beneficial effects of ranolazine.